2010
DOI: 10.1007/s10722-009-9528-x
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation and distribution of indica and japonica rice varieties along the altitude gradients in Yunnan Province of China as revealed by InDel molecular markers

Abstract: Indica-japonica variation represents the most significant genetic differentiation in Asian cultivated rice (Oryza sativa L. subsp. indica Kato or subsp. japonica Kato). Understanding the differentiation and distribution patterns of cultivated rice along altitude gradients will facilitate strategic utilization and conservation of rice germplasm from mountainous regions. In this study, we analyzed 203 varieties and 14 wild accessions of rice collected from localities across an altitude gradient between 450 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 27 publications
1
25
0
Order By: Relevance
“…For example, japonica cultivars are mainly cultivated in temperate environment at high latitudes or altitudes with cool climate conditions, while indica cultivars are usually grown in tropical and subtropical regions at low latitudes or altitudes16. To assess differences in chemical composition between japonica and indica sub-species, we compared their mature seed metabolomes.…”
Section: Resultsmentioning
confidence: 99%
“…For example, japonica cultivars are mainly cultivated in temperate environment at high latitudes or altitudes with cool climate conditions, while indica cultivars are usually grown in tropical and subtropical regions at low latitudes or altitudes16. To assess differences in chemical composition between japonica and indica sub-species, we compared their mature seed metabolomes.…”
Section: Resultsmentioning
confidence: 99%
“…Our landrace material consisted of only indica type cultivar grown from as low as 115-2,600 m above sea level and such broad zone of adaptation have been reported in indica type landrace in China across altitudinal cline from 450 to 2,350 m above sea level (Xiong 2010). The grouping based on altitude in our study corresponded well with significant differences found in morpho-physiological characters in landraces along altitude cline in 31 rice cultivars and 68 weedy strains (Ishikawa et al 2005), collected from some of the same sites in Bhutan.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, crop adaptation to agricultural practices and local conditions, through farmers’ seed selection, is also involved in crop diversity patterns (Mercer et al., ; Pressoir & Berthaud, ). The combination of seed selection and diffusion processes was notably involved in diversity patterns of barley in Ethiopia and rice in Yunnan, where particular landraces were circumscribed to specific elevations (Samberg et al., ; Xiong et al., ). Similar results were also reported for maize in Mexico where genetic differentiation among elevation zones was observed at a regional scale (van Heerwaarden, ), while other studies found that ethnolinguistic differences have a stronger impact than elevation at a local scale (Orozco‐Ramírez et al., ).…”
Section: Introductionmentioning
confidence: 99%